Earth Observation Data Processing in Distributed Systems - Petcu, D.; Panica, S.; Neagul, M.; Frîncu, M.; Zaharie, D.; Ciorba, R.; Dinįs, A. (Informatica)
Earth Observation Data Processing in Distributed Systems